Backsplash Galaxies - Muriel, Hernán; Coenda, Valeria (2021)
Abstract. We explore the properties of galaxies on the outskirts of clusters and their dependence on recent dynamical history in order to understand the real impact that the cluster core has on the evolution of galaxies.